2009
DOI: 10.1097/ccm.0b013e31819c0642
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous left ventricular assist in ischemic cardiac arrest

Abstract: During VF, a percutaneous LVAD may sustain vital organ perfusion. A potential clinical role of the device during cardiac arrest has yet to be established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Although the use of the Impella system has been extensively described in several cases of advanced cardiac failure [ 36 ], there are only a few reported studies of its use in the context of cardiac arrest, predominantly in post-cardiac arrest patients presenting with low cardiac output syndrome or recurring episodes of VF [ 37 ]. In three animal studies, Tuseth and colleagues showed that cerebral and myocardial perfusion could be significantly improved compared with open-chest cardiac compressions for up to 45 minutes [ 16 , 38 , 39 ]. However, they did not report whether this therapy had an influence on survival or neurological outcome in a closed-chest model of cardiac arrest and CPR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the use of the Impella system has been extensively described in several cases of advanced cardiac failure [ 36 ], there are only a few reported studies of its use in the context of cardiac arrest, predominantly in post-cardiac arrest patients presenting with low cardiac output syndrome or recurring episodes of VF [ 37 ]. In three animal studies, Tuseth and colleagues showed that cerebral and myocardial perfusion could be significantly improved compared with open-chest cardiac compressions for up to 45 minutes [ 16 , 38 , 39 ]. However, they did not report whether this therapy had an influence on survival or neurological outcome in a closed-chest model of cardiac arrest and CPR.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we did not directly measure cerebral or coronary blood flow during CPR, which has been extensively reported by Tuseth and colleagues in an open-chest cardiac arrest model [ 16 , 38 , 39 ]. However, because we decided to focus on resuscitation success and clinical outcomes, we were obliged to avoid invasive measurements that may have compromised survival itself.…”
Section: Discussionmentioning
confidence: 99%
“…Small studies comparing IABP and Impella in cardiogenic shock may indicate beneficial hemodynamic effects of the percutaneous LVAD [3,4]. Experimental studies have shown that Impella LP 2.5 ® may sustain vital organ perfusion even during cardiac arrest [6]. Thus, the percutaneous LVAD may have potential to significantly improve hemodynamics in selected critically ill patients.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, pVADs are effective tools for rapid hemodynamic stabilization in patients presenting with cardiogenic shock, and usually maintain vital organ perfusion even in case of cardiac arrest [25]. Although improvement of hemodynamic parameters by means of pVAD implantation are favorable compared with support by an IABP alone, it remains to be determined whether this benefi t translates into improved clinical outcome.…”
Section: Pvads During Cardiogenic Shockmentioning
confidence: 96%